Optimization of the procedure of thermal flaw detection of the honeycomb constructions by improving the accuracy of interference function - Storozhenko, V.; Orel, R.; Myagkiy, A. (My University, 2016)
The thermophysical model of the honeycomb constructions was explored. The given model considers the interferences, which appear on the OC surface, and those caused by the inhomogeneity of internal structure (by the “adhesion failure” flaw). The process of thermal flaw detection of honeycomb constructions was analyzed on its basis. As a result of the TFD analysis, a number of characteristic interferences, which complicate its industrial application, were revealed. The methods of decreasing interferences, characteristic for the honeycomb constructions, by optimization of the TFD procedure by the value of criterion ΔТdef/ΔU were proposed. Since the interferences, caused by inhomogeneous structure of the control object, cannot be removed by optimization of the TFD procedure, the method of processing the obtained results by the algorithm of differential filtration was proposed. As a result of applying proposed methods, we achieved a decrease in the interference level, connected with the heterogeneity of heating, to 0,7 °C (instead of 1,4 °C), a decrease in the interference, caused by the inhomogeneity of radiation capacity, to 0,6 °C (instead of 2 °C) and a decrease in temperature contrast, caused by the inhomogeneity of the glue layer, to 0,2 °C (instead of 1,2 °C). Owing to this, sensitivity of the thermal flaw detection to the identification of flaws, caused by inhomogeneity, increased: internal – to threshold dimension of a flaw from 6 mm to 3 mm, and reliability of their detection increased by 17–20 %.
Keywords: honeycomb constructions; thermal flaw detection; radiating capacity; adhesion failure